Changes in innate and adaptive immunity during human ageing 1 - De Maeyer, Roel (Henry Stewart Talks, 2022)
Ageing affects the immune system, T and B cells activity changes with age, Impaired ability to respond to new antigens, Increased frequency and severity of infections from established pathogens, loss of immune memory cells